Demographic and Psychosocial Characteristics Associated With Use of a Prostate Cancer Survivorship Website: Implications From a Multisite Randomized Controlled Trial - Allison Marziliano; Michael A Diefenbach; Shawna V Hudson; Erin K Tagai; Elizabeth A Handorf; Alicja Bator; Suzanne M Miller (JMIR Publications, 2022)
BackgroundMany prostate cancer (PC) survivors experience disease and treatment-related symptomatology in both the physical and psychosocial domains. Although the benefits and barriers to using web-based resources for cancer patients are well-documented, less research has focused on the personal characteristics important for efficient tailoring and targeting of information that are associated with usage. ObjectiveWe used the Cognitive-Social Health Information Processing (C-SHIP) framework to guide our exploration of personal characteristics associated with use of PROGRESS, an informational PC survivorship website that addresses physical, emotional, interpersonal, and practical concerns relevant for PC survivors. MethodsPC survivors (N=217) were randomized to the intervention arm (PROGRESS) of a randomized controlled trial. Of those randomized to the intervention arm, 84 used PROGRESS, and 133 did not use PROGRESS. Multivariable analyses evaluated demographic and psychosocial characteristics (eg, style of coping, health literacy, self-efficacy, affective states of depression, anxiety, and fatigue) associated with website use. ResultsA larger proportion of non-Hispanic White (68/160, 42.5%), compared with non-Hispanic Black (9/40, 23%), participants used PROGRESS (P<.001). Further, PROGRESS users were older in age (P<.001), had a monitoring style of coping (P=.01), and were less depressed (P=.004), anxious (P=.02), and fatigued (P<.001) than nonusers. Education, income, health literacy, blunting style of coping, self-efficacy, and treatment type (radiation therapy or surgery) were not significantly related to use. On multivariable analyses, race (OR 0.28, P<.001), age (OR 1.05, P<.001), monitoring style of coping (OR 1.27, P=.02), and overall mood (OR 0.98, P<.001) remained significant. ConclusionsA combination of monitoring and low levels of negative affect were associated with website use. Additionally, users were older, non-Hispanic White survivors. To ensure that important survivorship-relevant information reaches users, future efforts need to focus on enhancing patient engagement. Trial RegistrationClinicalTrials.gov NCT02224482; https://clinicaltrials.gov/ct2/show/NCT02224482